A new notion of convergence on ideal topological spaces - Granados, Carlos (2020)
In this article, we use the notions of b-open and b-I-open sets to introduce the idea of b-I-convergence which we will denoted by b-I-convergence, we also show some of its properties. Besides, some basic properties of b-I-Fréchet-Urysohn space is shown. Moreover, notions related to b-I-sequential and b-I-sequentially are proved. Furthermore, we show some relations of b-I-irresolute functions between preserving b-I-convergence functions and b-I-covering functions.